شبکات التواصل الاجتماعى ودورها فى تطویر خدمات المعلومات بمکتبات قصور الثقافة بمحافظة الاسکندریة :دراسة میدانیة - د. اسماء حسین محمد (المجلة الدولية لعلوم المكتبات والمعلومات)
Social networks play many social, cultural, educational, etc. roles in thelives of individuals in different cultures. There is no doubt that public librarieshave been heavily influenced by social networks in providing information servicesto the users. Therefore, any information specialist must make the best use of it tofill the gaps that his library cannot do, either for lack of time or for a tight budget.Also, social networks help the information specialist to provide what is new to theusers, as they always needs to know the new trends and waits the library toprovide him with.Public libraries in today's world are no longer as they were in the past,especially in the developed countries, because of their use of moderntechnologies that have emerged in the field of communications and informationtechnology, which became known as the “era of information and knowledge”,which imposed a new reality and cast a shadow over public libraries in all itsaspects and components. From: concepts and objectives through buildings,equipment, manpower, programs and services to planning, execution andevaluation. All this was covered by the winds of change and the introduction ofthese technologies became an important requirementThis study attempts to identify the importance of social networks indeveloping services provided by the public libraries affiliated to the GeneralAuthority for Cultural Palaces at Alexandria governorate as a public libraries thatneed to be presented with their services wherever the user resides and at anytime. Also, the public libraries should make all their services available throughtheir websites. The study also tries to know the extent of the impact of social  networks to increase the number of users of the services of these libraries, alsoThe study attempts to serve as a guide that can be used by libraries of culturalpalaces through proposals that will increase the effectiveness of benefiting fromits services in the age of social networks.The study based on the field survey methodology to determine theservices provided by the libraries of cultural palaces in Alexandria Governorate inthe era of social networks, and collecting facts and data, and then explainingthem to use their semantics in achieving the objectives of the study, One of themost important findings of the study that, social networks have helped to providebetter services, increasing the number of users from these libraries day after day